2000
DOI: 10.1053/jhep.2000.16332
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Prevents Pigment Gallstone Formation Induced by Bile Duct Ligation in Guinea Pigs

Abstract: Free radical-mediated oxidative stress has been implicated in the genesis of gallstone in vitro. This study was designed to examine the oxidative stress changes during pigment gallstone formation and to investigate whether melatonin (MLT) could act as a chemopreventive agent for cholelithiasis in a guinea pig model. The common bile duct of guinea pigs was ligated with or without MLT pretreatment. Animals were studied on day 7, 9, 12, and 14 after surgery. Stone and/or sludge developed in ligated guinea pigs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
(34 reference statements)
2
23
0
Order By: Relevance
“…In addition to liver and hepatic damage, free radical accumulation associated with bile duct ligation has been implicated in the genesis of gallstone (Eder et al, 1996). In this regard, antioxidant treatment with melatonin not only reversed the increased oxidative stress but also prevented gallstone formation (Shiesh et al, 2000). In our preparation, either prophylactic or therapeutic melatonin treatments were effective in reducing MDA levels and in increasing the endogenous antioxidant defense…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition to liver and hepatic damage, free radical accumulation associated with bile duct ligation has been implicated in the genesis of gallstone (Eder et al, 1996). In this regard, antioxidant treatment with melatonin not only reversed the increased oxidative stress but also prevented gallstone formation (Shiesh et al, 2000). In our preparation, either prophylactic or therapeutic melatonin treatments were effective in reducing MDA levels and in increasing the endogenous antioxidant defense…”
Section: Discussionmentioning
confidence: 63%
“…Recent evidence has shown that melatonin has protective effects on liver and hepatic injury after extrahepatic bile duct ligation in rats (Shiesh et al, 2000;Esrefoglu et al, 2005;Ohta et al, 2005). In addition to liver and hepatic damage, free radical accumulation associated with bile duct ligation has been implicated in the genesis of gallstone (Eder et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…A 5-gauge dull needle (0.5 mm in diameter) was placed beside CBD and tied together with 1-0 suture. After withdrawing the needle, incomplete stricture of CBD was achieved [12] . Abdominal wall was closed.…”
Section: Animalsmentioning
confidence: 99%
“…It was indicated that the animal model of incomplete stricture of CBD was successful [12] . It is verified that incomplete stricture of CBD could induce pigment gallstone formation [23] .…”
Section: Items S Group S+m Group C+m Group C Groupmentioning
confidence: 99%
“…This concentration, however, is sufficient for the oxidation of bilirubin (Eder, Miquel, Jongst, Paumgartner & von Ritter, 1996) in oxidative stress conditions, promoted by different endogenous (alterations of hormonal metabolism, infections) and exogenous (stress factors, sun bathing, light exposure) factors. Free-radical oxidation is involved in the pathogenesis of many pathological processes (Halliwell, Gutterigge & Cross, 1992), however, only a limited number of studies have been devoted to understand the role of oxidative processes in gallstones formation (Shiesh, Chen, Lin, Liu & Tsao 2000;Lightner et al, 1984). As a result of testing blood redox parameters of menopausal women with gallstone disease reduced activity of blood antioxidant ceruloplazmin/F 3+ -transferrin system and increased content of prooxidantsMn 2+ -ions were revealed.…”
Section: Discussionmentioning
confidence: 99%